Pandangan Yuridis Terkait Sistem Pengolahan Tanah Kas Desa - Gunawan, Mohammad Sigit; Karina, Siska (Universitas Ekasakti, 2023)
This research explores the juridical perspectives related to the village treasury land management system. The primary focus of this study is the analysis of legal aspects associated with the administration of village treasury land, including ownership, utilization, and regulations governing the system. Through a juridical approach, this research delves into the existing regulations, relevant policies, and legal viewpoints influencing the village treasury land management system. By understanding these juridical perspectives, it is anticipated that this study will contribute to the improvement and development of the village treasury land management system in accordance with applicable legal provisions.